Synchronization Attack to Chaotic Communication Systems - Zanin, Massimiliano; Sevilla-Escoboza, J. Ricardo; Jaimes-Reátegui, Rider; García-López, J. Hugo; Huerta-Cuellar, Guillermo; Pisarchik, Alexander N. (Discontinuity, Nonlinearity, and Complexity, 2026)
Synchronization of chaotic oscillators has an important application in cryptography. When two identical oscillators are coupled, they can be completely synchronized and the chaotic output of the transmitter oscillator can be used to mask a message. Although the oscillator parameters are usually used as secret keys, the sensitivity of such cryptosystems to parameter changes has never been systematically analyzed. To cryptanalyze a communication system based on synchro- nization of chaotic oscillators, we use a synchronization attack that allows estimating all unknown parameters by minimizing the synchronization error. Using this attack we cryptanalyze popular communication systems based on the Rössler and Chua chaotic electronic circuits. We suggest to include this attack as a standard security test for crypt-analysis of chaotic communication systems.